Grafts : writings on plants - Marder, Michael, 1980- (Univocal, 2016)
Grafting: do we ever do anything other than that? And are we ever free from vegetal influences when we engage in its operations? For the philosopher Michael Marder, our reflections on vegetal life have a fundamental importance in how we can reflect on our own conceptions of ethics, politics, and philosophy in general. Taking as his starting point the simple vegetal conception of grafting, Marder guides the reader through his concise and numerous reflections on what could be described as a vegetal philosophy. Grafts are transplants either of a shoot inserted into the trunk of another tree or, surgically, of skin (among other living tissues). They are delicate operations intended to preserve, improve, and modify both the grafted materials and the body that receives them. To graft is to create unlikely encounters, hybrid mixes, and novel surfaces. Moving across disciplinary lines, Grafts combines the lessons of plant science with the history of philosophy, semiotics, literary compositions, and political theory. Co-authoring some of the texts with other philosophers, plant scientists and artists, Marder allows their insights to be grafted onto his own, and vice versa. Weighing in on contemporary debates such as the ethics of biotechnology, dietary practices or political organization, Marder inserts an unmistakable vegetal perspective into topics of discussion where it normally wouldnt be found. Transferring the living tissue of his own texts into another context, he helps them live better, more fully, than otherwise.--